Деякі проблеми застосування джерел історії техніки (на прикладі історії зварювання) - Корнієнко, О.М.; Літвінов, О.П. (Питання історії науки і техніки, 2008)
Рассматриваются различные виды источников информации, которые можно использовать в качестве фактического материала для разработки истории отдельных
областей техники. От правильной оценки источников зависит точность исторических
исследований, определения приоритета и выполнения других задач. В числе надёжных
источников указываются первые научно-технические публикации, архивные материалы, патенты. Considered are different types of information sources which can be used as factual material
for development of the history of certain engineering fields. Accuracy of the historical
studies, determination of the priority, and accomplishment of other tasks depend upon the correct
assessment of the sources. The first scientific and technical publications, archival materials
and patents are identified as the reliable sources.